2017
DOI: 10.1055/s-0043-108252
|View full text |Cite
|
Sign up to set email alerts
|

Lung Metastasectomy for Pulmonary Metastatic Breast Carcinoma

Abstract: ABSTR AC TBreast carcinoma with pulmonary metastasis can be treated locally or systemically. Following primary tumour resection patients with isolated, completely resectable pulmonary nodules and definite functional operability can be offered lung metastasis resection. Following metastasectomy a median survival of 32 to 96.6 months can be achieved with corresponding five-year survival rates between 30.8 and 54.4 %. The procedure is associated with a mortality rate of 0 to 3 %. The most important independent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
(97 reference statements)
1
7
1
2
Order By: Relevance
“…In the present study, median survival from breast cancer diagnoses obviously varied by subtype, ranging from 8 months in triple-negative patients to 17 months in HR+/HER2+ patients. The median survival of all lung metastatic patients was 13 months, which was shorter than the 22 or 32 months reported in lung metastatic patients after treatment or metastasectomy in previous studies (Jin et al, 2018; Macherey et al, 2017; Welter et al, 2008). Although patients with lung metastases had poor prognoses, it was noteworthy that the 3-year and 5-year survival rate of patients was up to 33.9% and 17.8%, respectively.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In the present study, median survival from breast cancer diagnoses obviously varied by subtype, ranging from 8 months in triple-negative patients to 17 months in HR+/HER2+ patients. The median survival of all lung metastatic patients was 13 months, which was shorter than the 22 or 32 months reported in lung metastatic patients after treatment or metastasectomy in previous studies (Jin et al, 2018; Macherey et al, 2017; Welter et al, 2008). Although patients with lung metastases had poor prognoses, it was noteworthy that the 3-year and 5-year survival rate of patients was up to 33.9% and 17.8%, respectively.…”
Section: Discussioncontrasting
confidence: 59%
“…Although patients with lung metastases had poor prognoses, it was noteworthy that the 3-year and 5-year survival rate of patients was up to 33.9% and 17.8%, respectively. Prior studies have shown that the 5-year survival rate of lung metastatic patients from the first pulmonary metastasectomy was 36% or 30.8% (Macherey et al, 2017; Welter et al, 2008). Few studies have been able to reveal the association between the survival rate of breast cancer patients with lung metastases and various molecular subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…A daganatos betegek kivizsgálása, szoros kontrollja, utánkövetése során a mellkas-CT-felvételen már kismé-retű áttétek is felismerésre kerülnek. Szoliter tumorok -mint colorectalis [4], emlő- [5], vese- [6], fej-nyaki [7] daganatok és sarcomák [8], tüdő áttétei -esetén is hatékony kezelési forma azok műtéti eltávolítása, ami növeli a betegek túlélését. Szintén elsődlegesen VATS-technikával történő eltávolításuk javasolt, általában atípusos, nem anatómiai reszekcióval [9].…”
unclassified
“…Modern medical research has revealed that the formation and growth of tumors are associated with cellular differentiation and apoptosis ( 6 ). Apoptosis-induced inhibition of tumor cell proliferation is currently an effective method for treating tumors ( 7 ). After numerous years of development, traditional Chinese medicine has identified a set of unique antitumor methods ( 8 ).…”
Section: Introductionmentioning
confidence: 99%